Effect of the time taken on the performance of fabricated gas–solid fluidized bed column for the separation of rare earth elements - Nik Syahira, Nik Alias (2014)
A gas–solid fluidized bed separator used for the separation of rare earth elements (REEs) from printed circuit board was design and fabricated. In this work, the effect of time taken on the performance of the fabricated gas-solid fluidized bed column for the separation of rare earth elements was study. Waste from electronic devices was grinded to powder forms with the particles sized less than 1.0 μm were used in this study. Beds column with different heights of sampling port were analyzed at 10 cm, 20 cm, and 30 cm while the air pressure was 15 psi, 20 psi and 25 psi were tried in this investigation. The rare earth elements were subsequently analyzed by float–sink testing. The results showed the weight percent of the fine powder increases with increasing the time taken for collecting the sample. However, the separation density decreased with increasing the sampling port height of the column